Valve cells are crucial for efficient cardiac performance in Drosophila. - Christian Meyer; Achim Paululat (PLoS Genetics)
Blood flow in metazoans is regulated by the activity of the heart. The open circulatory system of insects consists of relatively few structural elements that determine cardiac performance via their coordinated interplay. One of these elements is the intracardiac valve between the aorta and the ventricle. In Drosophila, it is built by only two cells, whose unique histology represents an evolutionary novelty. While the development and differentiation of these highly specialised cells have been elucidated previously, their physiological impact on heart performance is still unsolved. The present study investigated the physiological consequences of cardiac valve malformation in Drosophila. We show that cardiac performance is reduced if valves are malformed or damaged. Less blood is transported through the heart proper, resulting in a decreased overall transport capacity. A reduced luminal opening was identified as a main reason for the decreased heart performance in the absence of functional valves. Intracardiac hemolymph flow was visualised at the valve region by microparticle injection and revealed characteristic similarities to valve blood flow in vertebrates. Based on our data, we propose a model on how the Drosophila intracardiac valves support proper hemolymph flow and distribution, thereby optimising general heart performance.